Plant diversity and conservation value of wetlands along a rural–urban gradient - du Toit, M.J.; du Preez, C.; Cilliers, S.S. (African Biodiversity & Conservation, 2021)
Background: Wetlands are the most threatened ecosystem in South Africa despite the range of ecosystem goods and services they provide. A significant cause of wetland destruction and degradation is a lack of understanding, by planners, policymakers and developers, of their ecological and socio-economic importance.Objectives: This study assessed the floristic composition and diversity of wetlands in the former Tlokwe Municipal area along a rural–urban gradient.Methods: Fourteen wetland sites were surveyed along an urbanisation gradient. Vegetation surveys were done in quadrats along transects in each wetland recording the cover-abundance of each species. The data were analysed by using ordinations, similarity percentages, and the adjusted Floristic Quality Assessment Index.Results: Overall, the proportional species composition of urban and rural wetlands was mainly similar. Trends indicated that the alpha diversity increased with both habitat size and heterogeneity along a rural–urban gradient. In all wetlands, indigenous species were the most abundant, with the highest score in the largest urban wetland. The floristic quality varied widely along the gradient with none of the sites in pristine condition.Conclusion: The similarity in species composition and floristic quality of the wetlands, as well as the high levels of indigenous species richness, indicated that urban wetlands are worthy of conservation. However, the signs of disturbances and the presence of alien species means that restoration strategies need to be implemented to improve the quality of the wetlands.